From Data Integration to Innovation Diffusion: The Role of Information Systems into Empowering Innovation Ecosystems - Araújo, Allysson Allex; Vilela, Ricardo; Accioly, Paola; Netto, Dorgival; Tomaz, Emerson B.; Câmara, Samuel (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Developing nations embrace innovation ecosystems for socioeconomic growth. However, Information Systems (IS) research on Brazil's innovation ecosystems is still quite scarce. We address this gap by examining the nexus between IS and innovation ecosystem by approaching the Diffusion of Innovation Theory to analyze the ''Mapa do Ecossistema de Inovação Cearense'' as a descriptive case study. We delve into this IS project's deployed features, challenges, and future avenues of research. This paper contributes by sharing insights for other regions interested in enhancing their innovation ecosystems and by raising awareness of the idea of IS in empowering them.